Optimization of photo fermentation in corn stalk through phosphate additive. (September 2019) - Liu, Huiliang; Zhang, Zhiping; Zhang, Quanguo; Tahir, Nadeem; Jing, Yanyan; Li, Yameng; Lu, Chaoyang
Abstract: Phosphorus is an essential nutrient for microbial growth which effectively influences the bio‑hydrogen production process. In the present study, the effect of phosphate concentration on simultaneous saccharification fermentation (SSF) hydrogen production by phototrophic microbial consortium has been investigated at various initial pH conditions (6, 7 and 8). The experimental results show that the hydrogen yield has been improved through the addition of phosphate, depending on initial pH and phosphate concentration. The maximum hydrogen yield of 63.09 ± 0.38 mL/g TS and highest energy conversion efficiency of 4.14 ± 0.02% from raw corn stalk were achieved at the phosphate concentration of 4 mmol/L with initial pH value of 6. We have shown that hydrogen yield for raw corn stalk can be enhanced by selecting appropriate amount of the additive. These results may help in optimization of the hydrogen production yield at industrial scale. Highlights: The effects of phosphate concentrations on SSF hydrogen production is investigated. The addition of phosphate significantly improved the hydrogen yield. Max. H2 yield achieved 63.09 ± 0.38 mL/g at 4 mM phosphate concentration with pH 6.